The Role Of Civil Society In Sustainable Agrarian Policy Advocacy - Syamsuddin Pasamai; Salle Salle (International Journal Labs, 2024)
Agrarian problems in Indonesia are still complex and have not been resolved completely. Inequality of land tenure, agrarian conflicts, environmental degradation, and land conversion are some examples of problems that continue to occur. In the midst of this situation, the role of civil society becomes important in fighting for sustainable agrarian policies. This research aims to analyze the role of civil society in agrarian policy advocacy in Indonesia. This research adopts a qualitative research method. Data collection is done through literature study. After the data is collected, the analysis is carried out in three stages, namely reducing data, presenting data, and drawing conclusions. The results show that the role of civil society in sustainable agrarian policy advocacy is very important in ensuring social justice, environmental protection, and strengthening the rights of farmers or indigenous peoples related to land. Civil society, through non-governmental organizations (NGOs) and activist networks, acts as a watchdog and critic of agrarian policies issued by the government. In addition, civil society also plays a role in providing education and understanding to local communities about their rights related to land, as well as mobilizing public support to strengthen their demands for equitable agrarian policies.